P152 Fluticasone furoate (FF)/Vilanterol (VI) once daily reduces asthma symptoms both day and night. (12th November 2015) - Leather, DA; Forth, R; Yates, L; Jacques, LA
Abstract : Introduction and objectives: FF/VI is the first once daily inhaled corticosteroid/long-acting b2 -agonist combination available for the treatment of asthma. Results from five phase III studies that have previously been presented demonstrated a sustained 24 h improvement in lung function and improvement in symptom-free 24 h periods. Methods: Post-hoc analyses of diary card data from these studies were performed to examine whether there was any difference in the contribution of the day and night time symptom-free period to the 24 h symptom-free period. The diary card scale used is described below. Day-time Symptom Score: 0 = No symptoms during the day 1 = Symptoms for one short period during the day 2 = Symptoms for two or more short periods during the day 3 = Symptoms for most of the day which did not affect my normal daily activities 4 = Symptoms for most of the day which did affect my normal daily activities 5 = Symptoms so severe that I could not go to work or perform normal daily activities Night-time Symptom Score: 0 = No symptoms during the night 1 = Symptoms causing me to wake once (or wake early) 2 = Symptoms causing me to wake twice or more (including waking early) 3 = Symptoms causing me to be awake for most of the night 4 = Symptoms so severe that I did not sleep at all To be counted as symptom-free during the day or night the patient needed to record a score of 0. Results: The post-hoc analyses demonstrated that the improvements in day and night time symptom –free periods were similar to the 24 h symptom free periods. See Figure 1 below. Conclusions: In general benefits in symptom free days and symptom free nights contributed to the benefit of FF/VI over comparator groups in terms of 24 h symptom free periods.